Activation of mucosal immunity as a novel therapeutic strategy for combating brucellosis - Pascual, David W.; Goodwin, Zakia I.; Bhagyaraj, Ella; Hoffman, Carol; Yang, Xinghong (Frontiers in Microbiology, 2022)
Brucellosis is a disease of livestock that is commonly asymptomatic until an abortion occurs. Disease in humans results from contact of infected livestock or consumption of contaminated milk or meat. Brucella zoonosis is primarily caused by one of three species that infect livestock, B. abortus in cattle, B. melitensis in goats and sheep, and B. suis in pigs. To aid in disease prophylaxis, livestock vaccines are available, but are only 70% effective; hence, improved vaccines are needed to mitigate disease, particularly in countries where disease remains pervasive. The absence of knowing which proteins confer complete protection limits development of subunit vaccines. Instead, efforts are focused on developing new and improved live, attenuated Brucella vaccines, since these mimic attributes of wild-type Brucella, and stimulate host immune, particularly T helper 1-type responses, required for protection. In considering their development, the new mutants must address Brucella’s defense mechanisms normally active to circumvent host immune detection. Vaccination approaches should also consider mode and route of delivery since disease transmission among livestock and humans is believed to occur via the naso-oropharyngeal tissues. By arming the host’s mucosal immune defenses with resident memory T cells (TRMs) and by expanding the sources of IFN-γ, brucellae dissemination from the site of infection to systemic tissues can be prevented. In this review, points of discussion focus on understanding the various immune mechanisms involved in disease progression and which immune players are important in fighting disease.